The representation of speech acts and language functions in Libya Public Preparatory English textbooks - Almahdi Alhodairy, Khadija Salem; Meganathan, Pavani Malaa (RSIS International, 2025)
Pragmatic competence involves understanding and applying sociocultural norms in communication, which is essential for effective language use. Despite grammatical and lexical proficiency, Libyan EFL learners often face challenges in real-life communication due to limited exposure to pragmatic language use, as English functions as a foreign language in Libya. Textbooks serve as key sources of pragmatic input, yet prior research has largely focused on secondary-level materials, overlooking preparatory textbooks. This study investigates the representation of speech acts and language functions in Libyan public preparatory English textbooks for Grades 7, 8, and 9, comprising three coursebooks and three workbooks. All dialogues from these textbooks were transcribed and compiled to reflect a range of communicative contexts and linguistic structures. Drawing on Searle’s (1976) speech act theory and Halliday’s (1978) language function theory, a mixed-methods approach was used. Quantitative data were obtained through systematic content analysis and analysed using SPSS, followed by qualitative interpretation. Findings showed a disproportionate emphasis on representative and directive speech acts, with minimal use of expressive and commissive acts and a complete absence of declarative acts. Similarly, language functions were largely limited to representational and personal uses, while instrumental, imaginative, and regulatory functions were scarcely represented. These imbalances may hinder the development of learners’ pragmatic competence. The study highlights the need for curricular reform and professional development to support the integration of a broader range of pragmatic elements. It emphasizes aligning textbook content with real-world communicative demands to better equip Libyan students for effective language use.